Variation of antioxidant activity and Phenolic content of some common home remedies with storage time - Shaik, Rahiman .; Tantry, Bilal Ahmad; Kumar, Avneesh . (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
The variation of antioxidant activity and total phenolic content of some plants commonly used as home remedies were screened on the basis of time factor such as methonlolic extracts of short term and long term air dried plant Ocimum sanctum (leaf), Cucumis sativus (Seed), and ethanolic extracts of Capsicum frutescens (Seed)and Coriandrum sativum(Seed). Antioxidant activities and total phenolic content values were estimated using DPPH reagent and Folin Ciocalteu reagent methods respectively. The antioxidant activity in short term air dried Ocimum sanctum plant methanol extract (IC50=0.03±0.01 mg/ l) stoods at the highest side than other plant extracts. On other side Coriandrum sativum plant ethanol extract represent higher phenolic content (70.24±3.4/66.57±4.1 mg/g) than other plant extracts. It was found that there is no correlation between antioxidant and phenolic content of these plant extracts and long term air dried samples had shown slight variation of antioxidant activities and total phenol contents from short term dried samples. Methanol extract of Ocimum sanctum. plant had shown statistical significance in antioxidant activity (short term IC50 0.03±0.01mg/dl, long term IC500.05±0,01mg/dl) than other study extracts These findings have high significance in the ageing of food chemistry.